2021
DOI: 10.1016/j.pmedr.2021.101547
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity is adversely associated with psychological distress, anxiety and depression during the COVID-19 pandemic

Abstract: Early COVID-19 pandemic data showed a spike in both food insecurity and poor mental health. The purpose of this study was to examine the relationship between food insecurity and mental health outcomes nine months after the start of the COVID-19 pandemic. A national survey of adults 18 years and older was administered in December 2020 (N=8,355). Multivariable logistic models and post-estimation margins commands were used to show the predicted probability of mental health outcomes (psychological distress, anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
4
8
0
Order By: Relevance
“…Mild food insecurity increases the prevalence of anxiety by 49%. This is consistent with a study that found that 2 out of 5 adults with low and very low food security have higher rates of anxiety prevalence [ 44 ]. Another study reported that 39% of participants scored positive for anxiety and 44% presented food insecurity (17% low food security and 27% very low food security).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Mild food insecurity increases the prevalence of anxiety by 49%. This is consistent with a study that found that 2 out of 5 adults with low and very low food security have higher rates of anxiety prevalence [ 44 ]. Another study reported that 39% of participants scored positive for anxiety and 44% presented food insecurity (17% low food security and 27% very low food security).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, it was found that moderate food insecurity is associated with a 73% increase in the prevalence of depressive symptoms. This is consistent with a study that found that 2 out of 5 adults with low food security have a 41.7% increased prevalence of depression and among adults with very low food security there is a 48.1% increased prevalence of depression [ 44 ]. This is also similar with a study that found that very low food security was associated with a 7.49-fold higher prevalence of depression (95% CI: 5.52–10.80) [ 45 ].…”
Section: Discussionsupporting
confidence: 92%
“…The results suggest that FI during the pandemic was associated with symptoms of GAD and MDD. Regarding the study hypothesis, a positive association proportional to severity was observed between FI and GAD and MDD symptoms, which confirms previous findings that addressed the association between lack of food access and mental health deterioration ( Fang et al, 2021 ; Polsky & Gilmour, 2020 ; Sundermeir et al, 2021 ). However, this study explored how the social and economic factors affect the association between FI and mental health.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, there is little evidence of an association between FI and mental health in stressful contexts, such as the COVID-19 pandemic ( Fang et al, 2021 ; Polsky & Gilmour, 2020 ; Sundermeir et al, 2021 ), especially in Brazil ( Santos et al, 2021 ). Therefore, including these variables in this study's analyses is justified by the intensification of inequalities during the COVID-19 pandemic, and the interdependence between sociodemographic characteristics and FI ( Tarasuk, St-Germain, & Mitchell, 2019 ) and mental disorders ( Cheah et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study that examined food insecurity and mental health among low-income Americans during the COVID-19 pandemic found that food insecurity increased the risk of depression and anxiety by 257% and 253%, respectively. [19] Similar findings were also observed in other studies investigating the impact of food insecurity on mental health during the pandemic [20,21]. Uncertainty over one's ability to maintain a steady supply of food or acquire food in the future may be a source of chronic stress that increases symptoms of anxiety and depression [22,23].…”
Section: Introductionsupporting
confidence: 74%